The evolution and expression of stomatal regulators in C3 and C4 crops: Implications on the divergent drought tolerance - Song, Zhuojun; Wang, Le; Lee, May; Yue, Gen Hua (Frontiers in Plant Science, 2023)
Drought stress is a major environmental hazard. Stomatal development is highly responsive to abiotic stress and has been used as a cellular marker for drought-tolerant crop selection. C3 and C4 crops have evolved into different photosynthetic systems and physiological responses to water deficits. The genome sequences of maize, sorghum, and sugarcane make it possible to explore the association of the stomatal response to drought stress with the evolution of the key stomatal regulators. We show that C3 and C4 plants exhibit different drought responses at the cellular level. Drought represses the growth and stomatal development of C3 crops but has little effect on that of C4 plants. In addition, stomatal development is unresponsive to drought in drought-tolerant C3 crops but is repressed in drought-tolerant C4 plants. The different developmental responses to drought in C3 and C4 plants might be associated with the divergent expression of their SPEECHLESS genes. Particularly, C4 crops have evolved to generate multiple SPEECHLESS homologs with different genetic structure and expression levels. Our research provides not only molecular evidence that supports the evolutionary history of C4 from C3 plants but also possible a molecular model that controls the cellular response to abiotic stress in C3 and C4 crops.